Colchicine causes prenatal cell toxicity and increases tetraploid risk - Ding Wang; Yingjun Xie; Minyi Yan; Qianying Pan; Yi Liang; Xiaofang Sun (BMC, 2019)
Abstract Background Colchicine is a clinical medicine used for relief from gout and familial Mediterranean fever. Because of its toxic effects, intravenous injection of colchicine has been banned, but it is still widely administered orally. We assayed the toxic effects of colchicine in cultured primary chorionic villus cells and amniotic fluid cells to interpret its influence on the placenta and foetus. Methods Bright field record and cell count kit 8 were used to value cell viability. Flow cytometer was used to identify cells markers, cell cycle and cell apoptosis. G-banding was used for karyotype analysis for sample genetic and drug effect evaluation. Results Chorionic villus cells and amniotic fluid cells were characterized as mesenchymal cells that share most cell surface markers and have a similar response to colchicine. Colchicine did not induce a decline in cell viability at low concentrations but suppressed cell proliferation by arresting the cell cycle in the G2/M phase and increased the risk of tetraploid generation in a small subset of cases. Conclusions Our study revealed the results of a colchicine-induced toxicity test in prenatal cells and determined the anti-mitotic biologically functional dose and manner of administration that might reduce the risk of tetraploid generation.